Perbandingan Pengungkapan (Disclosure) Informasi Keuangan Di Neraca dan CALK (LKPD Aceh Barat Daya) - Naupal Alfarisyi (Jurnal Ilmiah Ekonomi Terpadu (Jimetera), 2021)
bstract This paper contains a comparison of the disclosure of financial information in the balance sheet and notes to the financial statements of LKPD Aceh Barat Daya. The phenomenon that appears in the disclosure is a discrepancy between the existing information and that which is disclosed to users of financial statements, including the public, which if not disclosed honestly will lead to a crisis of confidence in local governments. This paper is structured to show a comparison of disclosures and discuss how this level of disclosure relates to the confidence of local governments in providing financial information. This paper has been prepared by reviewing the literature so that it can be concluded that the disclosures in LKPD Aceh Barat Daya between the balance sheet and notes to the financial report are presented quite well. Keywords: agency theory,disclosure, signalling theory